Budidaya Rumput Laut Untuk Peningkatan Kesejahteraan Ekonomi - Ariwibowo, Muhammad Eko; Darma, Sapta Setia; Septanta, Rananda (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The purpose of this community service is to provide information on how to increase the potential of natural resources located in Pamulang Permai, which is an area that has quite high potential in the seaweed plant business in general, but currently it has not been utilized optimally by the local community at this time. , most of the seaweed plants that are produced are immediately sold individually without knowing the harvest that the accounting information system consumes. This is due to a lack of innovation from the local community. Therefore, seaweed cultivation is one way that can be done by harvesting quite small or large areas of land that can be put to good use, maintain nutritional value, and increase economic value. With the empowerment of cultivation, it is hoped that it can help improve the economy of the people of South Tangerang and take advantage of the harvest of seaweed plants for social welfare which is more durable to give rise to various innovations in processing seaweed itself in a sustainable manner.